Modern Aspects of Bulk Crystal and Thin Film Preparation - Kolesnikov, Nikolai; Borisenko, Elena (InTechOpen, 2012)
In modern research and development, materials manufacturing crystal growth is known as a way to solve a wide range of technological tasks in the fabrication of materials with preset properties. This book allows a reader to gain insight into selected aspects of the field, including growth of bulk inorganic crystals, preparation of thin films, low-dimensional structures, crystallization of proteins, and other organic compounds.